Karakteristik struktur dan kebahasaan teks deskripsi siswa di sekolah menengah pertama islam terpadu - Meli Rahmadani (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
The purpose of this research is to describe the characteristics of the structure and language of the description text of the VII grade students of SMP IT Al-Kahfi Pasaman Barat. This type of research is qualitative research using descriptive methods. The results of this research are two, namely (1) characteristics of the structure of the description text of the VII grade students of SMP IT Al-Kahfi Pasaman Barat is the title, identification, and description of the section, and (2) the linguistic characteristics of the description text of the VII grade students of SMP IT Al-Kahfi Pasaman Barat is special words, synonymous words with strong emotions, and personal pronouns.